Developing a scale for examining the perspective of university students on parental care - Peng, Xuxin; Nakatani, Hisae; Chen, Huifang; Inoue, Yuriko; Song, Fang; Yoshihara, Mikako; Lei, Ruxin (Frontiers in Psychology, 2023)
With the declining birth rate and increasingly aging population in Japan, an increased care burden may be placed on the family and the younger generation will address challenging circumstances when they can care for their parents. This study aimed to develop a scale for examining the perspectives of Japanese university students on parental care and determines its reliability and validity. A web-based survey on a total of 408 Japanese students was adopted. This study performed exploratory and confirmatory factor analyses to obtain the underlying factors of the scale. Reliability was verified using Cronbach's α coefficient and Spearman-Brown's split-half reliability α coefficient. Validity was verified through sample, criterion-related, and convergent and discriminant validity. In total, the study identified a three-factor 11 item-scale. Cronbach's α for the scale was 0.901, and the Cronbach's α and split-half reliability α coefficients of each factor were greater than 0.7. Three factors explained 64.6% of the total variance. The model indicators were χ2/df = 2.241, comparative fit index (CFI) = 0.951, incremental fit index (IFI) = 0.951, TLI = 0.942, root mean square error of approximation (RMSEA) = 0.078 (p < 0.001). Thus, the study confirmed that the convergent and discriminant validity is acceptable. Correlations were noted for criterion-related validity (r = 0.675, p < 0.001). The results show that the scale for examining the perspective of Japanese university students on parental care was confirmed with good reliability and validity.